Culture and production of Lucilia sericata Meigen (1826) larvae for rearing stinging catfish Heteropneustes fossilis (Bloch, 1794) using poultry waste (Asian Journal of Medical and Biological Research, 2022)
The fly larvae (Lucilia sericata) are being used as an alternative protein source in any kind of animal feed as it reduces the cost of preparation of feed. This current study focused on the physico-chemical and proximate properties of raw poultry waste, while this study also revealed the production process of fly larvae and the proximate composition of it. The poultry waste was collected from Suvro poultry farm, Sutiakhali, Mymensingh, then the physic-chemical properties of the raw poultry waste were determined using different procedures. Three treatments were considered for production of fly larvae, T1 (3 kg), T2 (6 kg) and T3 (9 kg) in a 15 kg capacity tray with three replications. After production, the proximate composition were also measured of fly larvae. Physico-chemical properties such as, color, odor, texture, temperature, pH, total solids (TSS+TDS), chemical oxygen demand, dissolved oxygen, alkalinity, available N, available P, and fiber in raw poultry waste were determined and presented. Proximate composition such as, moisture, total N, total P, available N, total Ca, ash and crude fiber were found in significant amount in the poultry waste. It was found that T3 (1350±68g) produced highest volume of live maggot compared to the other treatments, but T2 (17.50±1.10%) produced highest percentage volume. The proximate compositions of fly larvae were assessed and found 56.60±0.25% protein value in it, suggesting that fly larvae could be the protein replacer in fish feed. The result of this study revealed cheap protein source in aquaculture production, such as production and rearing of stinging catfish Heteropneustes fossilis, and the findings might be helpful for cost reduction in aquaculture operation.Asian J. Med. Biol. Res. 2022, 8 (4), 216-224